2015
DOI: 10.1016/j.ijsu.2015.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic distal gastrectomy reduced surgical site infection as compared with open distal gastrectomy for gastric cancer in a meta-analysis of both randomized controlled and case-controlled studies

Abstract: LDG was associated with a lower incidence of SSI, especially wound infection, as compared with ODG in a meta-analysis of both RCTs and CCSs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…These findings regarding pulmonary complications and pneumonia are supported by the results of other meta-analyses comparing LTG with OTG [3, 6]. In one meta-analysis comparing LDG with ODG, LDG reduced the risk of postoperative pneumonia slightly but not significantly [24]. Moreover, in a Korean RCT comparing LDG with ODG in patients with early gastric cancer, LDG was associated with a slightly but not significantly lower risk of pulmonary complications [25].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These findings regarding pulmonary complications and pneumonia are supported by the results of other meta-analyses comparing LTG with OTG [3, 6]. In one meta-analysis comparing LDG with ODG, LDG reduced the risk of postoperative pneumonia slightly but not significantly [24]. Moreover, in a Korean RCT comparing LDG with ODG in patients with early gastric cancer, LDG was associated with a slightly but not significantly lower risk of pulmonary complications [25].…”
Section: Discussionmentioning
confidence: 72%
“…Many of the studies included in the present meta-analysis reported less operative bleeding but a longer operative time in LTG than in OTG. In a meta-analysis of LDG that included matched CCSs, the incidence of wound infection was lower in LDG than in open distal gastrectomy (ODG) [24]. In a Korean RCT comparing LDG with ODG in patients with clinical stage I gastric cancer, LDG significantly reduced wound complications such as wound infection and dehiscence [25].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy as a minimally invasive technique has been confirmed could significantly reduce the incidence rate of postoperative surgical site infections [25]. A systematic review was conducted through comparing the surgical site infection rate between laparoscopic and open distal gastrectomy and found that laparoscopic approach was associated with a lower incidence rate of surgical site infection, especially wound infection [26]. A lower incidence of wound infection was also found for patients undergoing laparoscopic resection of colorectal cancer in comparison with those receiving an open approach [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the meta-analysis conducted by Xiong et al, the abdominal abscess rate in patients undergoing laparoscopic total gastrectomy was lower than patients undergoing open approach, but the difference was not statistically significant [29]. Moreover, in the more recent systemic reviews and meta-analysis which contained more patients undergoing laparoscopic major gastrointestinal surgeries also reported there were no significant differences in abdominal abscess between the laparoscopic and the open approaches [26, 30, 31]. Thus, debate remains about the surgical approaches regarding abdominal abscess.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic procedure could improve the postoperative clinical course, reduces the incidence of postoperative pneumonia and surgical site infection compared with open procedure [17] [18]. Furthermore, laparoscopic procedure is able to protect the gut drying and reduce the abdominal well trauma [19].…”
Section: Discussionmentioning
confidence: 99%